The role of financial analysis in ensuring economic security of agricultural enterprise - E. V. Bannikova; E. V. Provalova; V. E. Provalov (Омский научный вестник: Серия "Общество. История. Современность")
Financial analysis is important for ensuring the economic security of an economic entity, since this aspect implements the protection of the financial interests of a commercial organization in the process of its life. As a result, it becomes necessary to consider financial analysis from a practical point of view, namely, carrying out specific calculations of various indicators characterizing the financial condition of the organization, namely, the solvency, liquidity and financial stability ratios. Therefore, the research topic that is chosen in this graduate work is relevant today.